Selection Capability: How Capability Gaps and Internal Social Frictions Affect Internal and External Strategic Renewal - Capron, Laurence; Mitchell, Will (Organization Science, 2009)
The dynamic capabilities literature suggests that firms need to use both internal development and external sourcing to thrive over time, but we have a limited understanding of the conditions that best suit different sourcing choices. This study examines how constraints that arise from firms' existing stocks of capabilities and from their internal social contexts shape their choices of capability-sourcing modes and, in turn, their ability to obtain new capabilities. Thus, the research focuses on an underemphasized form of dynamic capability: the ability to select appropriate modes of capability sourcing. We test the arguments with a survey and longitudinal survival study of the international telecommunications industry. We find intriguing variations in the way that firms' selection capability influences their ability to renew their capabilities and, ultimately, to survive.